2017
DOI: 10.1051/0004-6361/201731595
|View full text |Cite
|
Sign up to set email alerts
|

Anti-correlation between multiplicity and orbital properties in exoplanetary systems as a possible record of their dynamical histories

Abstract: Context. Previous works focused on exoplanets discovered with the radial velocity (RV) method reported an anti-correlation between the orbital eccentricities of the exoplanets and the multiplicity M (i.e., the number of planets) of the systems they inhabit. Aims. We further investigate this reported anti-correlation here using a dataset comprising exoplanets discovered with both the RV and transit methods, searching for hints of its causes by exploring the connection between the number of planets and the dynam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 11 publications
6
30
1
Order By: Relevance
“…• Mass ratio (µ = M pl /M ) and orbital eccentricity are very influential in determining a system's overall dynamical stability. In particular, we find that even moderate orbital eccentricities can prove to be destabilising, a finding that re-enforces the results of several studies that highlight the inverse relationship between multiplicity and eccentricity (Carrera et al 2016;Agnew et al 2017;Zinzi & Turrini 2017).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…• Mass ratio (µ = M pl /M ) and orbital eccentricity are very influential in determining a system's overall dynamical stability. In particular, we find that even moderate orbital eccentricities can prove to be destabilising, a finding that re-enforces the results of several studies that highlight the inverse relationship between multiplicity and eccentricity (Carrera et al 2016;Agnew et al 2017;Zinzi & Turrini 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Even more impressive is the range of destabilisation in semi-major axis in Figure 5c, reaching out in both directions to the locations of the 3 : 1 inner resonance and the 1 : 4 outer resonance with the planet's orbit in the highest eccentricity case we examined (e pl = 0.3). In contrast, the unstable regions in the circular case only reached to the 5 : 3 inner, and just beyond the 1 : 2 outer respectively, re-enforcing the significance of even moderate orbital eccentricities on multiple system stability (Zinzi & Turrini 2017).…”
Section: Effect Of Eccentricitymentioning
confidence: 87%
See 1 more Smart Citation
“…The first statistical studies of their orbital properties revealed the existence of an anti-correlation between the number of planets in planetary systems (i.e. a parameter also indicated as multiplicity) and their average eccentricities (Limbach & Turner 2015;Zinzi & Turrini 2017). Planets inhabiting systems with low multiplicity on average possess higher orbital eccentricities than planets in systems with high multiplicity, a trend holding from systems with multiplicity of two to the multiplicity of eight of the Solar System (Zinzi & Turrini 2017).…”
Section: Planetary Migration: Ariel's Best Allymentioning
confidence: 99%
“…a parameter also indicated as multiplicity) and their average eccentricities (Limbach & Turner 2015;Zinzi & Turrini 2017). Planets inhabiting systems with low multiplicity on average possess higher orbital eccentricities than planets in systems with high multiplicity, a trend holding from systems with multiplicity of two to the multiplicity of eight of the Solar System (Zinzi & Turrini 2017). This trend suggests that processes of chaotic exchange are widespread among multi-planet systems (Zinzi & Turrini 2017), supporting the idea that migration by planetplanet scattering plays an important role in shaping the structure of planetary systems.…”
Section: Planetary Migration: Ariel's Best Allymentioning
confidence: 99%